ANALISIS HUKUM PROGRAM ASPIRASI DEWAN PERWAKILAN RAKYAT PROVINSI SULAWESI BARAT DALAM PEMENUHAN KEPENTINGAN RAKYAT - Abdul Rahim; Rezki Amalia Wahyuni Mustakim (Indonesian Journal Of Law Studies, 2022)
Aspiration of the people is the duty of the Parliament of West Sulawesi province in order to improve people's welfare. In carrying out the aspirations, DRPD have the legal provisions regulating the function of the budget, supervision and legality. With the program's aspirations DPRD West Sulawesi province, is expected to improve the welfare of people in West Sulawesi. The purpose of this study was to determine the forms of aspiration program undertaken by legislators of West Sulawesi and to know the aspirations of program implementation undertaken by legislators of West Sulawesi province in fulfilling the needs of the people. The location of this research is the Parliament of West Sulawesi province with the informant research was chairman of the parliament, five legislators of West Sulawesi and one staff DPRD of West Sulawesi province. Long time research as much as three months with the type of research is descriptive and historical. Data collection techniques used were observation, interviews and documents, while the technique of the analysis of the data used is a qualitative approach was preceded by efforts to uncover the truth and honesty of research subjects. The research result was the role of Parliament West Sulawesi province in building and increasing public participation in the patterns of aspiration of society is used for this, not only refers to the rules / rules of applicable law, but many use a variety of ways that is effective, this to make it easier for legislators to get or obtain an aspiration of people of all walks of life. Suggestions in this research is the need for dissemination of the program's aspirations Parliament, increased cooperation with village institutions and improvement system within Parliament administarasi West Sulawesi province